2015
DOI: 10.1186/s12977-015-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

Activated regulatory T cells suppress effector NK cell responses by an IL-2-mediated mechanism during an acute retroviral infection

Abstract: BackgroundIt is well established that effector T cell responses are crucial for the control of most virus infections, but they are often tightly controlled by regulatory T cells (Treg) to minimize immunopathology. NK cells also contribute to virus control but it is not known if their antiviral effect is influenced by virus-induced Tregs as well. We therefore analyzed whether antiretroviral NK cell functions are inhibited by Tregs during an acute Friend retrovirus infection of mice.ResultsSelective depletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 55 publications
2
36
1
Order By: Relevance
“…The IL-2 mAb S4B6 complex has already been shown to improve NK cell responses and subsequent clearance of tumor cells [100, 149]. In the FV model, an up to 90% reduction in viral loads was demonstrated after specific stimulation of NK cells with IL-2 mAb S4B6 complex [100]. In this study, proliferation and maturation of NK cells as well as activation and effector functions were significantly improved.…”
Section: Therapeutic Approaches To Augment Nk Cell Responses In Retrosupporting
confidence: 59%
See 2 more Smart Citations
“…The IL-2 mAb S4B6 complex has already been shown to improve NK cell responses and subsequent clearance of tumor cells [100, 149]. In the FV model, an up to 90% reduction in viral loads was demonstrated after specific stimulation of NK cells with IL-2 mAb S4B6 complex [100]. In this study, proliferation and maturation of NK cells as well as activation and effector functions were significantly improved.…”
Section: Therapeutic Approaches To Augment Nk Cell Responses In Retrosupporting
confidence: 59%
“…It was therefore likely that retrovirus-induced Tregs also inhibit antiviral NK cell responses. Indeed, we recently demonstrated that specific ablation of Tregs in FV infected mice improved the activation, cytokine production, and cytotoxic activity of NK cells [100]. Competition for IL-2 was found to be the main molecular mechanism of Treg–NK cell suppression (Fig.…”
Section: Counter-regulation Of the Nk Cell Response By Retrovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation of IL2Rα (CD25) could result in differences in the ability of CD56 bright NK cells to respond to IL‐2 stimulation. Alternatively, modulation of CD25 may result in a gain of immunomodulatory potential by making CD56 bright NK cells able to regulate the availability of IL‐2 in the microenvironment, a feature previously described for Tregs .…”
Section: Resultsmentioning
confidence: 94%
“…Influence of regulatory T cell depletion on the outcome of infection has been shown in several models. Littwitz‐Salomon et al showed a strong increase of NK cell maturation, activation and effector functions in Treg‐depleted mice, and activated regulatory T cells suppressed effector NK cell responses by an IL‐2‐mediated mechanism during an acute retroviral infection. Another study showed a significantly increased IL‐6 level and a trend toward higher levels of TNF‐α in Treg‐depleted mice during sepsis, which supported the hypothesis that the hyper‐inflammatory response during the early phase of sepsis was intensified in mice lacking Treg cells.…”
Section: Discussionmentioning
confidence: 99%